Analytical applications of microbial fuel cells. Part II: Toxicity, microbial activity and quantification, single analyte detection and other uses - Abrevaya, Ximena Celeste (2014)
Microbial fuel cells were rediscovered twenty years ago and now are a very active research area. The reasons behind this new activity are the relatively recent discovery of electrogenic or electroactive bacteria and the vision of two important practical applications, as wastewater treatment coupled with clean energy production and power supply systems for isolated low-power sensor devices. Although some analytical applications of MFCs were proposed earlier (as biochemical oxygen demand sensing) only lately a myriad of new uses of this technology are being presented by research groups around the world, which combine both biological?microbiological and electroanalytical expertises. This is the second part of a review of MFC applications in the area of analytical sciences. In Part I a general introduction to biological-based analytical methods including bioassays, biosensors, MFCs design, operating principles, as well as, perhaps the main and earlier presented application, the use as a BOD sensor was reviewed. In Part II, other proposed uses are presented and discussed. As other microbially based analytical systems, MFCs are satisfactory systems to measure and integrate complex parameters that are difficult or impossible to measure otherwise, such as water toxicity (where the toxic effect to aquatic organisms needed to be integrated). We explore here the methods proposed to measure toxicity, microbial metabolism, and, being of special interest to space exploration, life sensors. Also, some methods with higher specificity, proposed to detect a single analyte, are presented. Different possibilities to increase selectivity and sensitivity, by using molecular biology or other modern techniques are also discussed here.